Türkiye'de teknolojik gelişme sorunsalı açısından üniversite-sanayi işbirliğinin değerlendirilmesi - Araman, Sinan (My University, 2009)
Competition among capitalist companies has greatly increased in today’s world. Capitalist countries take parts in this competition in order to gain influence and competitive edge over other countries in world trade system. Likewise Turkey has a desire to improve its standing in the capitalist hierarchy by implementing science and technology policies. Neo-liberalism is a new stage in the continuity of the capitalist productivity and it has gradually made science and universities more dependent upon the requirements of the capitalist companies. Co-operation between universities and industry has been functionalised in this context. This process converts the notion of science into a commodity and converts scientific productivity into an activity is determined by market demands and it has also increased the inequality and the hierarchy and has given rise to contradiction relate to the capitalism.
Keywords: Ekonomi; Teknolojik Gelişme_Türkiye; Üniversiteler ve Yüksekokullar